Towards Learning Standards in Economics in Australia. Issue 1 (19th March 2013) - Guest, Ross
<x xml:space="preserve">Abstract</x> This paper discusses the development of learning standards in higher education economics in Australia. The motivation is twofold. The creation of Tertiary Education Quality Standards Agency in 2011, along with the revised Australian Qualifications Framework specifications published in July 2011, have given the learning standards agenda a new impetus in Australia. Work has been done overseas on learning standards in economics through the UK Benchmarking Statement and the OECD's Assessment of Higher Education Learning Outcomes study. However, a key finding from learning standards projects in Australia in other disciplines is that the Australian academic community needs to take ownership of the standards agenda as a pre‐condition for general acceptance and successful implementation. Second, the development of learning standards in economics is an opportunity to drive an evidence‐based process of curriculum renewal, including critical reflection on core knowledge, skills and assessment methods.